Pelatihan Model Pembelajaran RADEC dalam Mengembangkan Proyek Penguatan Profil Pelajar Pancasila di SDN 01 Leuwiliang - Lestari, Hana; Rahmawati, Ima (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
P5 was implemented in the independent curriculum to implement the values of Pancasila to Indonesian students. P5 stands for the Pancasila Student Profile Strengthening Project. This program aims to provide opportunities for students to learn about important issues around them. This community service activity aims to provide training in the form of developing a RADEC (Read, Answer, Discuss, Explain, Create) learning model that can be implemented for the Pancasila student profile strengthening project. The targets of this community service are teachers of SDN 1 Leuwiliang, Bogor Regency, totaling 55 people. The approach or service method used is Service Learning (SL). The Service Learning method is one approach to teaching that combines academic goals to foster awareness in solving problems directly. The implementation of community service in the development of the RADEC learning model for elementary school teachers has satisfactory results, as many as 85.67% of teachers can develop teaching modules that implement the RADEC model in strengthening the Pancasila student profile, and the teacher's response states that the RADEC learning model is easy to design and can develop competencies in the project of strengthening the Pancasila student profile.